2012
DOI: 10.1002/pd.4013
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional ultrasound and maternal bonding, a third trimester study and a review

Abstract: Bonding increases after either a 3D/4D or 2D US. The effect of 3D/4D US on bonding is stronger at better degrees of visibility and recognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 37 publications
(152 reference statements)
2
39
0
Order By: Relevance
“…These attachment emotions initially occur when the pregnant woman feels the first fetal movement, but continue with advanced medical technology, continuously establishing attachment between pregnant woman and her fetus throughout gestation [10]. The ultrasound scan is one such technology that can satisfy a pregnant woman's curiosity by producing images of the unborn baby [12].…”
Section: Using Technology In Maternal-fetal Attachmentmentioning
confidence: 99%
See 3 more Smart Citations
“…These attachment emotions initially occur when the pregnant woman feels the first fetal movement, but continue with advanced medical technology, continuously establishing attachment between pregnant woman and her fetus throughout gestation [10]. The ultrasound scan is one such technology that can satisfy a pregnant woman's curiosity by producing images of the unborn baby [12].…”
Section: Using Technology In Maternal-fetal Attachmentmentioning
confidence: 99%
“…Several recent studies compared the levels of prenatal emotional attachment for different dimensional ultrasounds [1,10,12,20,21]. Righetti et al [10]revealed no difference in the maternal antenatal attachment score betweenthree-dimensional (3D) or four-dimensional (4D) and 2D ultrasound scanning groups.…”
Section: Using Technology In Maternal-fetal Attachmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Although studies have not shown 3D/4D ultrasound to be any more effective than 2-dimensional ultrasound when it comes to improving bonding scores or reducing parental stress and anxiety [1], elective ultrasound sessions may allow greater involvement of siblings and other family members and may provide more time for the ultrasound than would be possible in a busy sonography unit.…”
Section: William Goodnight Nancy Chescheirmentioning
confidence: 99%